2017
DOI: 10.1080/1360080x.2017.1411062
|View full text |Cite
|
Sign up to set email alerts
|

A career in professional services: accident, serendipity or something more?

Abstract: As part of a larger study, professional staff from two universities, Australian and British, were asked how they entered into a higher education career and what factors kept them in that career. Many participants reported that they found themselves in professional services almost by accident, or by a fortunate combination of circumstances. However, in addition to the serendipitous recruitment reported in earlier studies, our analysis found a positive value associated with higher education that attracted people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…In addition, accidents or health problem, positive and negative work experiences are also defined as chance events. Other studies based on participant opinions about chance report similar results (Kim et al, 2019;Ulas-Kilic et al, 2020;Regan & Graham, 2018). In these studies, chance events frequently reported were personal or business relationship.…”
Section: Chance Eventssupporting
confidence: 58%
See 2 more Smart Citations
“…In addition, accidents or health problem, positive and negative work experiences are also defined as chance events. Other studies based on participant opinions about chance report similar results (Kim et al, 2019;Ulas-Kilic et al, 2020;Regan & Graham, 2018). In these studies, chance events frequently reported were personal or business relationship.…”
Section: Chance Eventssupporting
confidence: 58%
“…However, talking with family and close relatives was perceived as a chance when asked what chance events were. Similarly, in many studies, the relationships of participants were perceived by them as a chance factor (Betsworth & Hansen, 1996;Bright et al, 2005a;Hirschi, 2010, Kim et al, 2019Korkut-Owen, 2018;Ulas-Kilic et al, 2020;Regan & Graham, 2018). Participants describe it as a chance to have a family that supports them or to benefit from the experiences of family and close friends.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…SDT has been used as a lens for understanding the intrinsic motivations of both professional services (Graham, 2013;Regan & Graham, 2018) and academic staff (Fein, Ganguly, Banhazi, & Danaher, 2017). By extension, we argue that SDT can serve as a useful framework for understanding the motivations of TE managers, and for reflecting upon, evaluating and critiquing professional practice, professional development and career progression.…”
Section: T3: Self-determination Theorymentioning
confidence: 82%
“…Education is associated with doing good, making a difference, playing an important role, and will therefore be a positive environment for finding work. For some participants, education being a 'public good' matched their personal values, offering a more altruistic alternative to the perceived profit focus of the corporate world [2]. Therefore, higher education has an important role in developing careers and building the mental health of students to achieve a better quality and life planning.…”
Section: Introductionmentioning
confidence: 99%